Kemal Tahir'in romanlarında ve hikâyelerinde yapı-tema - Dere, Mustafa (My University, 2019)
Cumhuriyet dönemi Türk Edebiyatı’nın önemli ve tartışmalı yazarlarından biri olan Kemal Tahir, romancılığı ve hikâyeciliği bakımından özgün ve dikkat çeken bir edebî kimliğe sahiptir. Bu özellik, onun anlatı unsurlarını kullanımı ve eserlerinin içeriği dolayısıyladır. Kemal Tahir, Türk toplumunu ilgilendiren meseleleri sosyalist çerçevede, tahlile dayanan ayrıntılı bir bakış açısıyla değerlendirmiş ve bunu roman tekniklerini kullanarak kurguya taşımıştır.

Kemal Tahir, one of the most important and controversial writers of Turkish literature in the Republic period, has a unique and outstanding literary identity in terms of his novelism and storytelling. This feature is due to his use of the elements of narrative and the content of his works. Kemal Tahir made use of the issues concerning the Turkish society with a detailed perspective based on analysis within the socialist framework and integrated this into fiction by using novel techniques.
Keywords: hikâye; History and criticism; inceleme; Kemal Tahir; Kemal Tahir, 1910-1973; novel; review; roman; story; structure; Tarih ve eleştiri; tema; theme; Turkish literature; Türk edebiyatı; yapı